Mountainside murder - Helm, Nicole (Helm, Nicole. North star., 2021)
"North Star undercover operative Sabrina Killian is on a hit man's trail. She doesn't need help from Wyoming search and rescue ranger Connor Lindstrom. But the persistent ex-SEAL is the killer's target--and soon they are both being hunted. Now they've joined forces to uncover a treasonous conspiracy. But will Sabrina's and Connor's most dangerous secrets even the odds--or take them out for good?"--